Choosing antihypertensive treatment for a South African population - M.T. Mpe (South African Family Practice)
There is no uniform agreement as to which antihypertensive drugs should be given for initial therapy. All of the antihypertensive agents are roughly equally effective, producing a good antihypertensive response in 30 to 50 percent of cases. Thus, in uncomplicated cases, the choice of an antihypertensive drug is not generally made on the basis of efficacy. There is, however, wide inter-patient variability as many patients will respond well to one drug but not to another. There are also some predictable differences, such as black patients generally responding better to monotherapy with a thiazide diuretic or calcium channel blockers (CCBs), and relatively poorly to ACE (angiotensin-converting enzyme) inhibitors or beta blockers.